Co-crystallization in polyolefin blends studied by various crystallization analysis techniques - Sweed, Muhamed (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2006.